Simultaneous Penile and Signet Ring Cell Bladder Carcinoma in Renal Transplant Recipient: A First Case - Francesca Manassero; Gianluca Giannarini; Davide Paperini; Andrea Mogorovich; Greta Alí; Ugo Boggi; Cesare Selli (The Scientific World Journal)
The incidence and prevalence of cancer increase with time after transplantation. Therefore, a risk-adapted screening process is very important in order to identify low-grade malignancies early in their development. This provides the opportunity to initiate appropriate immunosuppressive regimens depending on the tumor type and stage of development. The first case presented is one of a 65-year-old patient with a double genitourinary carcinoma (penis and bladder). The patient received kidney transplantation 7 years prior to this event. After adequate surgical treatment (partial amputation of the penis for squamous cell carcinoma and complete transurethral resection of bladder adenocarcinoma), the patient was noted to be free of tumor recurrence and had functioning renal graft with a 2-year follow-up.